Antileukemogenesis of nypa fruticans on acute lymphoblastic leukemia – a preliminary study in vitro - Mamat, Suhana; Fadzir, Ummu Afifah; Zainudin, Muhammad Fauzan; Rosdi, Athirah; Abdul Wahab, Ridhwan; Hashim, Ridzwan (2015)
Background: Leukemia is one of the common cancers worldwide. Although the treatment options available for most type of cancers, but some of them remain incurable and the re-occurrence of disease is also common in many patients. Furthermore, modern therapy also leads to many side effects. All of these lead us to study on the possible anticancer activity of local fruit known as Nypa fruticans or locally known as nipah.